VITAMIN E SHIELDS AGAINST ALCOHOLIC TOXICITY BY SAFEGUARDING HEPATIC PARENCHYMAL MORPHOLOGY AND LOWERING BLOOD ALT LEVELS - Noman Ullah Wazir; Shabir Hussain; Farzana Salman; Momina Haq; Munaza Khattak; Shamaila Wadud (Journal of Ayub Medical College Abbottabad, 2024)
Background: Alcohol consumption can have detrimental effects on the liver, as it plays a crucial role in processing and detoxifying substances in the body, including alcohol. Alcohol has the potential to hinder the liver’s capacity, which results in a variety of metabolic imbalances and deficiencies. This research aimed to investigate alterations in the liver tissue due to alcohol administered orally, along with exploring the potential protective effects of vitamin E against these alterations. Methods: An assortment of male pet rabbits (totalling 18) was part of the study. The categorized groups included: Control group A, which received normal saline as a placebo treatment. Experimental group B, administered with an oral dose of a 30% ethanol solution mixed with normal saline. Experimental group C, given an oral dose of a combination containing a 30% ethanol solution, vitamin E, and normal saline. At the end of experiment, blood samples were obtained to assess ALT levels, and liver tissue sections were stained with Hematoxylin and Eosin for microscopic analysis of hepatocyte structure. Results: Highly significant differences between the blood ALT levels, hepatocyte count/size/nuclear count/size, sinusoids size in control and experimental groups were observed. Vitamin treated rabbits showed preserved morphology of hepatocytes as compared to non-vitamin treated rabbits during alcohol consumption by showing less ballooning of hepatocytes and shrinkage of nuclei which are the main initial signs of hepatocytes damage. Conclusion: Frequent alcohol intake leads to swift alterations in liver tissue and blood ALT levels over brief spans, yet these effects may be reduced through the antioxidative properties of vitamin E.